Short-term stability of resting heart rate variability: influence of position and gender - Young, F. L. S.; Leicht, A. S. (Applied Physiology, Nutrition, and Metabolism, 2010)
Heart rate variability (HRV) is utilized within laboratory and clinical settings as a noninvasive indicator of cardiac autonomic modulation. Past research has utilized a wide variety of resting methodologies and, as such, it is difficult to draw conclusions on the nature of HRV from different studies. Therefore, the current study aimed to assess the short-term stability of resting HRV during a 40-min resting trial and the impact of body position and gender on this short-term stability. Resting HRV was determined from 40-min trials in 3 standard positions (supine, seated, and standing) for healthy males (n = 14) and females (n = 16). Time-domain, geometric, and frequency-domain measures of resting HRV were examined during consecutive 10-min segments using a 3-way ANOVA (time × position × gender) and Tukeys` post-hoc tests with reproducibility assessed by intraclass correlation coefficients (ICC) and coefficients of variation. During rest, most HRV measures fluctuated over time, were greater in the supine compared to the standing position, and were greater for males compared with females. Variables that reflected primarily vagal modulations of heart rate remained stable, whereas other HRV measures varied over time. The majority of HRV variables exhibited substantial to excellent short-term reproducibility (ICC > 0.6) with time-domain and geometric measures of HRV demonstrating greater values compared with frequency-domain parameters. Based on the current results, the recording and analysis of HRV at 0-10 min of rest was recommended as a standardized protocol for the assessment of resting HRV in any standard position for either gender during laboratory and (or) clinical settings.